Comparisons of economic thresholds for Asian citrus psyllid management suggest a revised approach to reduce management costs and improve yield - Chen, Xue Dong; Stockton, Dara; Gossett, Hunter; Qureshi, Jawwad A.; Ibanez, Freddy; Pelz-Stelinski, Kirsten S.; Stelinski, Lukasz L. (Frontiers in Sustainable Food Systems, 2022)
Huanglongbing (HLB) or citrus greening disease is transmitted by the Asian citrus psyllid, Diaphorina citri Kuwayama. Vector control is considered a basic component of HLB management even under high disease incidence scenarios. While vector management relies on chemical sprays, overuse of insecticides raises several concerns including insecticide resistance, environmental impacts, and secondary pest outbreaks. The present study compared the effects of three different economic thresholds (ET-0.2, 0.5, 1.0) and one calendar-based application schedule on the incidence of D. citri and beneficial species in plots of commercially grown citrus, as well as end-of-season yield and overall management costs. The results suggest that reducing spray frequency from 8 to as little as 3 sprays per year had little effect on counts of pest and beneficial insects in the field. The numbers of D. citri and that of a secondary weevil pest were similar between plots treated with the calendar-based spray plots and plots managed with the ET-1.0. Furthermore, spider numbers were higher in the ET-1.0 plots, while ant numbers were lower compared with calendar sprayed plots. Management input costs were lower under economic thresholds (ET-0.5 to ET-1.0) than with monthly calendar-based sprays, while yield losses were only slightly greater in the lower threshold of 0.2 mean psyllids per tap than with calendar sprays. Overall, management savings of more than 100 % made up for this difference. Together, these results suggest that implementing a spray program of rotated chemistries based on an economic threshold of 0.5-1.0 adult psyllids per stem tap could provide both economic and ecological benefits. We discuss the implications of such an approach in the context of a young citrus tree protection program and the greater goals of sustainable citrus production under HLB.